A kind of condensed particles and its preparation method and application
By using cationic polymers containing nitrogen functional groups as a coagulant, agglomerated particles with long oxidation induction period and low yellowing index were prepared, which solved the problems of poor thermal oxidation resistance and insufficient antibacterial and mildew resistance in the prior art, and achieved excellent impact resistance, thermal oxidation resistance and antibacterial and mildew resistance of resin composite materials.
Patent Information
- Application Number
- CN202411456033.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In the prior art, acid or metal salt commonly used as latex copolymers for aromatic vinyl graft copolymers will lead to poor thermal oxidation resistance of the agglomerated particles, high yellowing index, and antibacterial and mildew-resistant properties affect the safety and service life of the resin composite material.
The cationic polymer with nitrogen-containing functional groups is used as a coagulant, and the ratio with the vinyl polymer is within the range of 0.2 to 27 parts to prepare agglomerated particles with a long oxidation induction period and a low yellowing index as an impact modifier to improve the impact resistance of the resin composite material, and achieve antibacterial and mildew-proof effect through electrostatic interaction.
It achieves good thermal oxygen aging resistance, low yellowing index and excellent antibacterial and mildew resistance of condensed particles, extends the service life of the resin composite material, and improves its impact resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of latex coagulation materials, and in particular relates to coagulation particles and a preparation method and application thereof. Background Art
[0002] Aromatic vinyl graft copolymers, such as butadiene-styrene-acrylonitrile copolymer (ABS), butadiene-methyl methacrylate-styrene-acrylonitrile copolymer (MABS), butadiene-methyl methacrylate-styrene copolymer (MBS), acrylonitrile-styrene-acrylate monomer copolymer (ASA), etc., are widely used in various fields such as electronics, automobiles, and daily necessities due to their excellent physical and mechanical properties.
[0003] Aromatic vinyl graft copolymers can be prepared by a variety of methods, such as bulk polymerization, suspension polymerization, solution polymerization and emulsion polymerization. Compared with other methods, emulsion polymerization is more likely to obtain latex with a large molecular weight, a specific particle size or a grafted structure, and is a more commonly used synthesis method. However, emulsion polymerization produces latex. To obtain a solid product, a coagulant needs to be added to separate the polymer from the latex to form latex agglomerated particles. The latex agglomerated particles can be used as a good toughening agent to prepare resin composite materials and improve their impact resistance.
[0004] At present, the coagulants commonly used in the latex of aromatic vinyl graft copolymers are acids or metal salts; however, when acids or metal salts are used for coagulation, the residual coagulants will cause the obtained coagulated particles to have poor heat-oxidation resistance and high yellowing index, which will in turn affect the heat-oxidation resistance and yellowing resistance of the resin composite material. In addition, the resin composite material will cause a large number of bacteria to breed under long-term use and accumulation, threatening food safety and human health; and the existing technology mostly improves the antibacterial and mildew-proof properties of the resin composite material by adding antibacterial agents; however, inorganic antibacterial agents, such as silver ion antibacterial agents, ZnO series antibacterial agents, etc., will affect the heat-oxidation resistance of the resin composite material; and polymer antibacterial agents will affect the mechanical properties of the resin composite material.
[0005] Therefore, developing a kind of condensed particles with excellent impact resistance, heat-oxidative aging resistance, and antibacterial and mildew-proof properties is an urgent problem to be solved in this field. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a condensed particle and a preparation method and application thereof. The condensed particle has a long oxidation induction period, a low yellowing index, and good thermal oxygen aging resistance; it can be used as an impact modifier to improve the impact resistance, thermal oxidation resistance and aging yellowing resistance of the resin composite material, and at the same time, make the resin composite material have excellent antibacterial and mildew resistance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In the first aspect, the present invention provides a condensed particle, wherein the condensed particle includes a vinyl polymer and a coagulant; the coagulant includes a cationic polymer; the cationic polymer has a nitrogen-containing functional group in its molecular structure; based on 100 parts of the vinyl polymer, the amount of the cationic polymer added is 0.2 to 27 parts.
[0009] In the present invention, a cationic polymer with nitrogen-containing functional groups is selected as a coagulant, and the ratio of the cationic polymer to the vinyl polymer is within the above range, and the obtained coagulated particles have good resistance to heat and oxygen aging, a long oxidation induction period and a low yellowing index; the coagulated particles are used as an impact modifier to effectively improve the impact resistance of the resin composite material. At the same time, the cationic polymer with nitrogen-containing functional groups in the coagulated particles can kill bacteria and fungi through electrostatic interaction, so that the resin composite material has good antibacterial and mildew-proof properties and prolongs the service life of the resin composite material.
[0010] In the present invention, the amount of the cationic polymer added is 0.2 to 27 parts, for example, 0.2 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.2 parts, 10.5 parts, 10.8 parts, 11 parts, 11.2 parts, 11.5 parts, 11.8 parts, 12 parts, 12.2 parts, 12.5 parts, 12.8 parts, 13 parts, 13.2 parts, 13.5 parts, 13.8 parts, 14 parts, 14.2 parts, 14.5 parts, 14.8 parts, 15 parts, 15.2 parts, 15.5 parts, 15.8 parts, 16 parts, 16.2 parts, 16.5 parts, 16.8 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 26 parts, and ranges consisting of any two.
[0011] In the present invention, the addition amount of the vinyl polymer and the addition amount of the cationic polymer are both calculated based on solid mass, ie, the mass of the solvent is not included.
[0012] Preferably, based on 100 parts of the vinyl polymer, the amount of the coagulant added is 2 to 18 parts, more preferably 7 to 15 parts.
[0013] Preferably, the nitrogen-containing functional group includes at least one of an amide group, an amine group, an ammonium group, a guanidine group or a nitrogen-containing aromatic group, preferably at least one of an amine group, an ammonium group or a guanidine group.
[0014] Preferably, the cationic polymer includes at least one of chitosan, polyamino acids and derivatives thereof, polyhexamethylene biguanide and salts thereof, acrylic polymers containing quaternary ammonium groups, or polycarbonate polymers containing quaternary ammonium groups, and further preferably at least one of polyamino acids and derivatives thereof, polyhexamethylene biguanide and salts thereof, or acrylic polymers containing quaternary ammonium groups.
[0015] In the present invention, the "and" in the "polyamino acids and their derivatives, polyhexamethylene biguanide and their salts" refers to and / or relationships, for example, polyamino acids and their derivatives include polyamino acids and / or polyamino acid derivatives. If the same expressions are used below, they represent the same meanings.
[0016] Preferably, the polyamino acid and its derivatives include linear homopolymer polyamino acids, linear copolymer polyamino acids, branched homopolymer polyamino acids, branched copolymer polyamino acids, quaternized derivatives of the aforementioned polyamino acids, guanylated derivatives of the aforementioned polyamino acids, or at least one of the quaternized and guanylated derivatives of the aforementioned polyamino acids, and further preferably, the quaternized derivatives of the aforementioned polyamino acids, guanylated derivatives of the aforementioned polyamino acids, or at least one of the quaternized and guanylated derivatives of the aforementioned polyamino acids.
[0017] In the present invention, the "above-mentioned polyamino acid" refers to at least one of the above-mentioned "linear homopolymer polyamino acid, linear copolymer polyamino acid, branched homopolymer polyamino acid, branched copolymer polyamino acid".
[0018] Preferably, in the quaternized ammonium derivative of polyamino acid, the guanidinated derivative of polyamino acid, or the quaternized and guanidinated derivative of polyamino acid, the mass percentage of repeating units containing quaternary ammonium groups and / or repeating units containing guanidine groups is 50-100%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc.; more preferably, it is 70-100%, and more preferably, it is 90-100%.
[0019] In the present invention, part or all of the amino groups in the quaternized derivatives of polyamino acids, guanidinated derivatives of polyamino acids, or quaternized and guanidinated derivatives of polyamino acids are converted into quaternary ammonium groups and / or guanidino groups; when the mass percentage of repeating units containing quaternary ammonium groups and / or repeating units containing guanidino groups in the quaternized derivatives of polyamino acids, guanidinated derivatives of polyamino acids, or quaternized and guanidinated derivatives of polyamino acids is 100%, it indicates that all the amino groups in the molecular chain are quaternized and / or guanidinated.
[0020] Preferably, the monomers in the linear homopolymeric amino acid and the branched homopolymeric amino acid independently include any one of lysine, arginine, alanine, isoleucine, phenylalanine, tryptophan, histidine and glutamine, and more preferably arginine.
[0021] Preferably, the monomers in the linear copolymer amino acid and the branched copolymer amino acid independently include at least two of lysine, arginine, alanine, isoleucine, phenylalanine, tryptophan, histidine and glutamine.
[0022] In the present invention, the monomers in the linear copolymerized amino acid and the branched copolymerized amino acid each independently include at least arginine.
[0023] In the present invention, arginine contains guanidine groups in its molecular structure. Therefore, compared with other amino acids, the homopolymeric amino acids or copolymeric amino acids formed by arginine have better heat-oxidative aging resistance of the obtained condensed particles; the more guanidine groups there are, the better the performance of the condensed particles.
[0024] In the present invention, the cationic polymer can be purchased from the market or prepared by conventional methods.
[0025] Exemplarily, the preparation method of the linear homopolymer amino acid or linear copolymer amino acid comprises: the selected amino acid contains only one primary amine group and one carboxyl group, the amino acid monomer or its hydrochloride is mixed with an aqueous solution of an alkaline compound during homopolymerization and copolymerization, the mass ratio of the amino acid monomer or its hydrochloride to the aqueous solution of the alkaline compound is (2-5):1, and the reaction is carried out at 200-300°C for 20-50 min in the presence of a protective atmosphere, and the obtained product is precipitated and dried to obtain the linear homopolymer amino acid or linear copolymer amino acid. The aqueous solution of the alkaline compound includes but is not limited to an aqueous potassium hydroxide solution; the mass fraction of the aqueous potassium hydroxide solution is 10-30wt%. The difference between the preparation methods of the linear homopolymer amino acid and the linear copolymer amino acid is only that the monomer raw materials are different; when preparing a linear homopolymer amino acid, the monomer is an amino acid monomer; when preparing a linear copolymer amino acid, the monomer is an equimolar amount of different amino acid monomers.
[0026] For amino acid monomers containing two or more amino groups such as lysine, NCA-amino acid monomers (which can be commercially available or homemade) are used as raw materials, that is, the excess amino groups in the amino acid monomers are reacted with groups such as tert-butyloxycarbonyl, trifluoroacetyl or benzyloxycarbonyl, and the amino groups are protected to prepare NCA-amino acid monomers (N-carboxyl anhydride derivatives of amino acids), and then the NCA amino acid monomers are subjected to ring-opening polymerization. After the reaction, the above-mentioned groups (tert-butyloxycarbonyl, trifluoroacetyl or benzyloxycarbonyl) are removed by deprotection to obtain the linear homopolymer amino acid or linear copolymer amino acid.
[0027] The ring-opening polymerization method comprises: mixing NCA-amino acid monomer with a solvent to obtain an amino acid solution with a concentration of 0.1-0.4 g / mL; mixing an amine compound with a solvent to obtain an amine compound solution with a concentration of 2-20 mg / mL; mixing the amino acid solution and the amine compound solution, and stirring at room temperature for 24-96 h; subjecting the obtained reaction mixture to sedimentation and drying to obtain product A; and then deprotecting product A, the specific method comprising: mixing product A with trifluoroacetic acid to obtain a trifluoroacetic acid solution of product A with a concentration of 0.1 g / mL, adding 0.2-0.6 times the volume of trifluoroacetic acid to the trifluoroacetic acid solution of hydrogen bromide (the mass fraction of hydrogen bromide is 20-40 wt%), reacting at room temperature for 1-5 h, and then sedimenting and drying, re-dissolving the dried solid in water, adjusting the pH value to 8-10 with an alkaline compound, and sedimenting and drying again to obtain the linear homopolymer amino acid or linear copolymer amino acid. The amine compound includes but is not limited to propylamine; the solvent includes but is not limited to N,N-dimethylformamide (DMF).
[0028] Exemplarily, the preparation method of the branched homopolymeric amino acid and the branched copolymeric amino acid may be as follows:
[0029] An amino acid monomer or its hydrochloride is mixed with an aqueous solution of an alkaline compound in a mass ratio of (2-5):1, and reacted at 200-300°C for 20-50 min in the presence of a protective atmosphere. The obtained product is precipitated and dried to obtain the branched homo-amino acid or branched copolymer amino acid; the aqueous solution of the alkaline compound includes but is not limited to an aqueous potassium hydroxide solution; the mass fraction of the aqueous potassium hydroxide solution is 10-30wt%; the preparation methods of the branched homo-amino acid and the branched copolymer amino acid differ only in the different monomer raw materials; when preparing the branched homo-amino acid, the monomer is an amino acid monomer; when preparing the branched copolymer amino acid, the monomers are equimolar amounts of different amino acid monomers.
[0030] Exemplarily, the preparation method of the quaternary ammonium derivative of the polyamino acid includes: mixing the polyamino acid with a quaternary ammonium agent and a solvent to obtain a reaction solution; wherein the mass ratio of the polyamino acid to the quaternary ammonium agent in the reaction solution is (1-4):1, and the total concentration of the polyamino acid and the quaternary ammonium agent in the reaction solution is 0.02-0.1 g / mL; reacting the reaction solution at 30-60°C for 12-36 hours, settling, and drying to obtain the quaternary ammonium derivative of the polyamino acid; the polyamino acid includes a linear homopolymer polyamino acid, a linear copolymer polyamino acid, a branched homopolymer polyamino acid, or a branched copolymer polyamino acid; the quaternary ammonium agent includes a compound containing an acrylamide group and / or an ammonium group, such as an N,N-dimethyl-N-alkyl acrylamide compound, wherein the alkyl group can be a straight chain or branched alkyl group of C7-C18; or, a (2-acrylamideethyl) ammonium salt having different substituents on N, wherein the substituents include a straight chain or branched alkyl group of C1-C10.
[0031] Exemplarily, the method for preparing the guanidinium derivative of the polyamino acid comprises the following method:
[0032] A guanylating agent, potassium carbonate and an aqueous solution of polyamino acid (the mass fraction of polyamino acid is 1-4 wt%) are mixed to obtain a reaction solution (in the reaction solution, the molar amount of the guanylating agent and potassium carbonate is equal); the degree of guanylation modification of the polyamino acid can be adjusted by adjusting the mass ratio (or molar ratio) of the guanylating agent and the polyamino acid; the reaction solution is reacted at 40-80° C. for 6-24 h in the presence of a protective atmosphere, and then precipitated and dried to obtain a guanylated derivative of the polyamino acid; the polyamino acid includes a linear homopolymer polyamino acid, a linear copolymer polyamino acid, a branched homopolymer polyamino acid or a branched copolymer polyamino acid. The guanylating agent includes 1H-pyrazole-1-carboxamidine hydrochloride, methoxyisourea (or its sulfate), 2-ethyl-2-thiourea sodium hydrobromide, etc.
[0033] Exemplarily, the method for preparing the acrylic polymer containing a quaternary ammonium group may adopt a reversible addition-fragmentation chain transfer polymerization (RAFT polymerization) method; specifically, the method comprises:
[0034] The acrylate monomer is mixed with an initiator, a chain transfer agent and a solvent to obtain a reaction solution (the mass of the initiator is 0.05-1.5 wt% of the total mass of the acrylate monomer, the mass of the chain transfer agent is 5-20 wt% of the total mass of the acrylate monomer, and the total mass concentration of the acrylate monomer, the initiator and the chain transfer agent in the reaction solution is 180-240 mg / mL); the reaction solution is reacted at 60-90° C. for 4-12 h in the presence of a protective atmosphere, and the acrylate polymer is obtained through sedimentation, centrifugation and drying; the acrylate monomer is an acrylate containing an amine group, an ammonium group, a pyridine group, a pyrrole group, a pyrazole group, an indole group residue, or an acrylate containing the above groups can be obtained by simple treatment after polymerization, including but not limited to any one of (meth) acrylate aminoethyl and its salt, (meth) acrylate-2-indoleethyl ester or a combination of at least two thereof. The initiator includes but is not limited to azo initiators and / or organic peroxide initiators; the azo initiator includes but is not limited to azobisisobutyronitrile (AIBN); the peroxide initiator includes but is not limited to dibenzoyl peroxide (BPO). The chain transfer agent includes but is not limited to dithioester derivatives, and the dithioester derivatives include but are not limited to isopropyl dithiobenzoate (CDB), 2-cyano-2-propyl dodecyl trithiocarbonate, 2-cyano-2-propyl benzodisulfide, 2-phenylpropanethiothiobenzoate, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, etc. The solvent in the RAFT polymerization includes but is not limited to dimethyl sulfoxide (DMSO).
[0035] Exemplarily, the method for preparing the polycarbonate containing quaternary ammonium groups comprises:
[0036] The functionalized cyclocarbonate monomer is mixed with catalyst 1 and a solvent to obtain a mixed solution 1 (the mass of catalyst 1 accounts for 2-8 wt% of the mass of the functionalized cyclocarbonate monomer, and the total mass concentration of the catalyst and the functionalized cyclocarbonate monomer is 200-300 mg / mL); the obtained mixed solution 1 is mixed with an alcohol initiator (the amount added is 0.8-2.5 wt% of the mass of the functionalized cyclocarbonate monomer) and catalyst 2 (the amount added is 1-3 wt% of the mass of the alcohol initiator), and after stirring at room temperature for 10-60 min, an excess of benzoic acid is added to quench the catalyst; the obtained reaction product is then precipitated to obtain a white solid; the white solid is then mixed with a solvent (such as acetonitrile) to obtain a polycarbonate solution (the mass concentration of the polycarbonate is 0.015-0.05 g / mL); the polycarbonate solution is mixed with a quaternary ammonium agent (the molar ratio of the polycarbonate to the quaternary ammonium agent is 1:5-15), and stirred at room temperature for 8-24 h, purifying and drying the obtained product to obtain a polycarbonate containing a quaternary ammonium group; the functionalized cyclocarbonate monomer may contain an amine group, an ammonium group, a pyridine group, a pyrrole group, a pyrazole group, an indole group, or a six-membered ring acetal compound containing the above groups can be obtained by simple treatment after polymerization, including but not limited to 2,2-bishydroxymethyl formal propionate compounds; the catalyst 1 includes a compound containing a thiourea group, including but not limited to N-(3,5-trifluoromethylbenzene)-N′-cyclohexylthiourea (1-(3,5-bis(trifluoromethyl)-phenyl)-3-cyclohexyl-2-thiourea); the alcohol initiator may be a monohydric alcohol or a polyhydric alcohol, including but not limited to 4-methylbenzyl alcohol; the catalyst 2 includes an organic base, including but not limited to bicyclic amidine; the purification method includes but is not limited to dialysis; the drying method includes but is not limited to freeze drying; the quaternizing agent includes but is not limited to N-alkylammonium, wherein the alkyl group may be a saturated alkane or an unsaturated alkane with a chain length of C1 to C18, such as N-dimethylhexyl ammonium chloride.
[0037] Preferably, the molecular structure of the vinyl polymer includes any one or a combination of at least two of structural units derived from conjugated dienes, structural units derived from styrene and its derivatives, structural units derived from acrylonitrile and its derivatives, or structural units derived from (meth) alkyl acrylates.
[0038] Preferably, the molecular structure of the vinyl polymer includes structural units derived from conjugated dienes and structural units derived from styrene and its derivatives, and also includes at least one of structural units derived from acrylonitrile and its derivatives and structural units derived from alkyl (meth)acrylates.
[0039] Preferably, the mass percentage of the structural units derived from conjugated dienes in the vinyl polymer is 50-80%, for example, it can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%, 78.5%, 79%, 79.5%, 80%, and any two of the range values; preferably, it is 55-78%, more preferably, it is 60-75%; the mass percentage of the structural units derived from styrene and its derivatives is 5-25%, for example, it can be 5%, 5.5%, 6%, 6.5%, 7 %, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, and any two of the range values; preferably 11 to 20%, more preferably 12 to 18%; the balance is derived from structural units derived from acrylonitrile and its derivatives, and / or, derived from structural units of alkyl (meth)acrylates.
[0040] In the present invention, the mass percentage of each structural unit in the vinyl polymer is calculated based on the mass percentage of each monomer in the total monomers. For example, the mass percentage of the structural unit derived from conjugated diene in the vinyl polymer is 50-80%, which means that the conjugated diene monomer accounts for 50-80% of the total monomer mass.
[0041] In the present invention, the conjugated diene includes a conjugated diene with a carbon number of ≥4, illustratively including but not limited to butadiene, isoprene, hexadiene, heptadiene, nonadiene, etc.; the styrene and its derivatives include but are not limited to any one of styrene, α-ethylstyrene, α-methylstyrene, p-methylstyrene, o-tert-butylstyrene, bromostyrene or chlorostyrene (such as trichlorostyrene) or a combination of at least two; acrylonitrile and its derivatives include but are not limited to acrylonitrile, methacrylonitrile, fumaronitrile, etc. The (meth) alkyl acrylate includes but is not limited to methyl methacrylate, methyl acrylate, butyl methacrylate, butyl acrylate, etc.
[0042] In the present invention, the vinyl polymer includes at least one of butadiene-styrene-acrylonitrile copolymer (ABS), butadiene-methyl methacrylate-styrene-acrylonitrile copolymer (MABS), butadiene-methyl methacrylate-styrene copolymer (MBS) or acrylonitrile-styrene-acrylate monomer copolymer (ASA).
[0043] In the present invention, when the vinyl polymer is an acrylonitrile-styrene-acrylate monomer copolymer, the mass percentage of the structural unit derived from the (meth) alkyl acrylate is 50-85%.
[0044] Preferably, the oxidation induction period of the agglomerated particles in an air atmosphere at an isothermal temperature of 200° C. is ≥30 min, preferably ≥35 min, and more preferably ≥40 min.
[0045] Preferably, the a-value of the agglomerated particles measured by a Lab colorimeter is ≤10, preferably ≤8, and more preferably ≤5.
[0046] In the present invention, the moisture content of the agglomerated particles is relatively low, and the moisture content is less than 0.25%.
[0047] In the present invention, the moisture content (mass percentage) of the agglomerated particles is tested according to the method specified in GB / T 2914-2008 "Determination of volatile matter (including water) in plastic vinyl chloride homopolymer and copolymer resins".
[0048] In a second aspect, the present invention provides a method for preparing the agglomerated particles according to the first aspect, the preparation method comprising the following steps:
[0049] The agglomerated particles are obtained by mixing a latex of a vinyl polymer with a coagulant, subjecting the mixture to agglomeration and drying.
[0050] In the present invention, the latex of the vinyl polymer (solid content of 30-60%) can be purchased from the market, or prepared by a conventional method. Exemplarily, the preparation method comprises the following steps:
[0051] (1) A solvent, an initiator, a chain transfer agent, an electrolyte, an emulsifier and a surfactant in a formula amount of 20% are mixed uniformly at room temperature, and a conjugated diene monomer is added thereto in the presence of a protective atmosphere. After reacting at a temperature of 50-60°C and a rotation speed of 100-110 rpm for 6-12 h, the temperature is raised to 65-75°C and the rotation speed is raised to 110-125 rpm for 8-16 h, the temperature is further raised to 70-80°C and the rotation speed is raised to 135-135 rpm for 8-16 h, and then the remaining surfactant is added thereto. After stirring for 20-40 min, the temperature is lowered and the material is discharged to obtain a polyconjugated diene latex.
[0052] (2) The polyconjugated diene latex obtained in step (1), an initiator, a chain transfer agent, an emulsifier, a catalyst, a solvent and a grafting monomer (the grafting monomer includes at least two of styrene and its derivatives, acrylonitrile and its derivatives, and (meth) alkyl acrylate) are mixed, reacted at 50-60° C. for 1-6 hours, and then a surfactant is added thereto to continue the reaction for 0.5-3 hours to obtain the latex of the vinyl polymer.
[0053] In step (1) of the preparation method, the solvent includes water; based on 100 parts by mass of the conjugated diene monomer, the mass of the solvent is 80-120 parts; the initiator can be selected from commonly used initiators, including but not limited to one or more of potassium persulfate, ammonium persulfate or sodium persulfate; based on 100 parts by mass of the conjugated diene monomer, the mass of the initiator is 0.1-1 parts; the chain transfer agent can be selected from commonly used chain transfer agents, including but not limited to n-dodecyl mercaptan and / or tert-dodecyl mercaptan; based on 100 parts by mass of the conjugated diene monomer, the mass of the chain transfer agent is 0.2-1.2 parts; the electrolyte can be selected from commonly used electrolytes, including but not limited to sodium carbonate, One or more of sodium bicarbonate, sodium hydroxide, potassium carbonate or potassium hydroxide; based on the mass of the conjugated diene monomer as 100 parts, the mass of the electrolyte is 0.1~1 part; the emulsifier can be selected from commonly used emulsifiers, including anionic emulsifiers; the anionic emulsifier includes but is not limited to one or more of disproportionated rosin acid soap, stearic acid soap, oleic acid soap, tallow fatty acid soap, lauric acid soap, alkylbenzene sulfonate, and sulfate ester salt; based on the mass of the conjugated diene monomer as 100 parts, the mass of the emulsifier is 0.1~1 part; the surfactant includes an acetylene alcohol surfactant, which can play the role of an emulsifier, and commonly used acetylene alcohol surfactants can be used, including but not limited to one or more of methyl pentynol, 2,4,7,9-tetramethyl-5-decine-4,7,-diol, and ethyl octynol; based on the mass of the conjugated diene monomer as 100 parts, the total mass of the surfactant is 0.1~1 part.
[0054] In step (2) of the preparation method, the initiator, chain transfer agent, emulsifier, surfactant and solvent are selected from the same range of types as those in step (1); and the types of the components in step (1) and step (2) are the same or different; based on the mass of the polyconjugated diene latex as 100 parts by weight on a dry basis, the mass of the initiator, chain transfer agent, emulsifier and surfactant is independently 0.1 to 1 part; the catalyst can be a commonly used catalyst, including but not limited to tetramethylethylenediamine and / or sodium formaldehyde sulfite; based on the mass of the polyconjugated diene latex as 100 parts by weight on a dry basis, the mass of the catalyst is 0.2 to 2 parts, and the mass of the solvent is 100 to 140 parts.
[0055] Preferably, the coagulation is carried out under neutral conditions.
[0056] In the present invention, the neutral condition is adjusted by adding a pH adjuster, and the pH adjuster includes an organic acid and / or an inorganic acid; the functionality of the organic acid and / or the inorganic acid is 1 to 3, and is preferably sulfuric acid and / or acetic acid.
[0057] In the present invention, the mixing is carried out in a solvent, and the solvent includes water; the specific steps of the mixing include: using a pH regulator to adjust the latex of the vinyl polymer to neutrality; pre-mixing the cationic polymer with the solvent to obtain a coagulation liquid with a solid content of 4-10%; and then mixing the coagulation liquid with the latex of the vinyl polymer at 50-95°C according to a formula in which the addition ratio of the vinyl polymer to the cationic polymer is 100:0.2-27 (both the vinyl polymer and the cationic polymer are measured by solid weight).
[0058] In the present invention, the solid content of the coagulation liquid is selected so that the cationic polymer can be fully dissolved, thereby obtaining a solution with a lower concentration and better fluidity.
[0059] Preferably, the condensation includes condensation through the steps of first heat preservation, temperature increase, second heat preservation and temperature reduction.
[0060] Preferably, the temperature of the first insulation is 70-80°C, for example, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, etc.; the time is 1-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7min, 8 min, 9 min, 10 min, etc.
[0061] Preferably, the heating rate of the heating is 3-7°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, etc.
[0062] Preferably, the temperature of the second insulation is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc.; the time is 5-15 min, for example, it can be 5 min, 6 min, 7min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc.
[0063] Preferably, the cooling rate is 0.5-4°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, etc., down to room temperature.
[0064] In the present invention, before drying, the slurry obtained by coagulation is subjected to solid-liquid separation; the solid-liquid separation can be carried out by filtering, centrifugal dehydration or spray drying. In order to improve the whiteness of the coagulated rubber powder, the dehydrated rubber powder can be washed. The drying step can be hot air drying on a fluidized bed at a drying temperature of 50-70°C; or it can be extrusion dehydration on a wet extruder.
[0065] In a third aspect, the present invention provides a resin composition, which comprises, in parts by weight, 70 to 90 parts of resin (for example, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, and a range consisting of any two of them) and 10 to 30 parts of an impact modifier (for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, and a range consisting of any two of them); the impact modifier comprises the agglomerated particles described in the first aspect.
[0066] In the present invention, the agglomerated particles can be used as a good impact modifier and can be blended and kneaded with other resin materials to form a resin composition, and the impact strength of the resin composition can be improved as the content of the agglomerated particles increases. At the same time, the cationic polymer contained in the latex agglomerated particles has certain antibacterial properties, so that the agglomerated particles and the composition obtained by blending with certain resin materials also have good antibacterial and mildew-proof effects.
[0067] In the present invention, the resin includes at least one of styrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene-acrylonitrile terpolymer, polystyrene, polyvinyl chloride, polycarbonate, polypropylene, polyphenylene ether, polyester or polyamide.
[0068] Preferably, the antibacterial rate of the resin composition is ≥80%, preferably ≥90%, more preferably ≥95%, and particularly preferably ≥99.9%; and the mildew resistance grade reaches 0-1.
[0069] Preferably, the notched Izod impact strength of the resin composition is ≥24 kJ / m 2 , preferably ≥28kJ / m 2 , more preferably ≥30 kJ / m 2 .
[0070] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0071] Compared with the prior art, the present invention has the following beneficial effects:
[0072] The condensed particles provided by the present invention use a cationic polymer with a nitrogen-containing functional group as a coagulant, and the ratio of the cationic polymer to the vinyl polymer is within a specific range. The obtained condensed particles have good heat-oxidative aging resistance, a long oxidation induction period and a low yellowing index. The condensed particles are used as an impact modifier to effectively improve the impact resistance, heat-oxidative resistance and aging yellowing performance of the resin composite material, and at the same time, the resin composite material has excellent antibacterial and mildew-proof properties, thereby extending the service life of the resin composite material. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0074] Preparation Example 1: Preparation of latex of vinyl polymer (A)
[0075] Latex of vinyl polymer A1
[0076] Calculated by mass percentage, the molecular structure of the vinyl polymer A1 includes 68% of structural units derived from butadiene, 15% of structural units derived from styrene and 17% of structural units derived from acrylonitrile.
[0077] The preparation method of the latex of the vinyl polymer A1 comprises:
[0078] Step S1: 100 parts of water, 0.4 parts of ammonium persulfate, 0.6 parts of n-dodecyl mercaptan, 0.4 parts of sodium carbonate, 0.4 parts of potassium stearate and 0.08 parts of ethyl octynol are added to a reactor by mass, and stirred at room temperature until completely dissolved and mixed; nitrogen is introduced into the reactor to replace the air so that the oxygen content is less than 10 ppm, and then 100 parts of butadiene monomer are added according to the formula; the reactor is heated to 55°C and reacted at a constant temperature for 9 hours as the first stage polymerization reaction, and the stirring speed is controlled to 105 rpm; after the first stage polymerization reaction is completed, the system is heated to 70°C and reacted at a constant temperature for 12 hours as the second stage polymerization reaction, and the stirring speed is controlled to 120 rpm; after the second stage polymerization reaction is completed, the temperature is raised to 75°C and the constant temperature reaction is reacted for 12 hours as the third stage reaction, and the stirring speed is controlled to 130 rpm. At the end of the polymerization reaction, 0.32 parts of ethyl octynol are added, and the reaction is cooled and discharged after stirring for half an hour to obtain polybutadiene latex.
[0079] Step S2: The polybutadiene latex in step S1 is heated to 55°C, and based on 100 parts by weight of the dry basis of the polybutadiene latex, 0.4 parts of potassium persulfate, 0.6 parts of tert-dodecyl mercaptan, 0.4 parts of potassium oleate, 1 part of tetramethylethylenediamine and 120 parts of water are added thereto, and a formulated amount of acrylonitrile monomer and a formulated amount of styrene-based monomer are added, and the addition is continued dropwise for 2 hours. After the addition is completed, the reaction is continued for 3 hours, and then 0.4 parts of ethyl octynol are added. The reaction is continued at 55°C for 2 hours, and then the temperature is cooled to room temperature to obtain the latex of the vinyl polymer A1 with a solid content of about 32%.
[0080] Latex of vinyl polymer A2~A7
[0081] The preparation method of the latex of vinyl polymers A2 to A7 is the same as that of vinyl polymer A1, the only difference is that the types and masses of the structural units of the vinyl polymers are different, that is, the types and ratios of monomers are different (the total amount of monomers is the same), calculated in terms of mass percentage (the total amount of monomers is 100%), and the specific formula is shown in Table 1; wherein, “ / ” indicates that the component is not included in the formula.
[0082] Table 1
[0083]
[0084] Preparation Example 2: Preparation of cationic polymer (B)
[0085] Cationic polymer B1
[0086] Linear poly-ε-lysine: purchased from Aladdin, product number P303210-25g;
[0087] Cationic polymer B2
[0088] Linear poly-α-lysine
[0089] The preparation method comprises: dissolving 10 g of Nε-benzyloxycarbonyl-L-lysine cyclic anhydride (purchased from Sichuan Jiayinglai Technology Co., Ltd.) monomer in 45 mL of anhydrous N,N-dimethylformamide (DMF), then adding 5 mL of 10 mg / mL DMF solution of propylamine thereto, stirring at room temperature for 72 h, and then precipitating the obtained reaction mixture in ether and vacuum drying to obtain a white powder (8.47 g). Then, 7.5 g of the white powder is dissolved in 75 mL of trifluoroacetic acid, and 30 mL of 33wt% hydrogen bromide acetic acid solution is added thereto, and the reaction is reacted at room temperature for 3 h. Then, ether is used for precipitation, and water is subsequently added to the precipitate for rotary evaporation and drying. The obtained solid is dissolved in water, adjusted to a pH of 9 with sodium hydroxide, and then precipitated with ether and vacuum dried to obtain linear poly-α-lysine.
[0090] Cationic polymer B3
[0091] Branched poly-lysine
[0092] The preparation method comprises: adding 91.32 g of lysine hydrochloride and 28.05 g of KOH solution (20 wt%) into a 500 mL round-bottom flask, connecting a water separation device, pumping nitrogen three times, each time for more than 10 minutes, and finally maintaining a nitrogen atmosphere, stirring and heating the reaction at 250° C. for 30 minutes, stopping heating, dissolving the obtained product with methanol and precipitating it in ether, and vacuum drying to obtain branched polylysine.
[0093] Cationic polymer B4
[0094] Partially guanylated linear poly-α-lysine (the mass of the repeating unit containing guanidine groups accounts for 50% of the total mass of partially guanylated linear poly-α-lysine)
[0095] The preparation method includes: using a guanidinating agent to guanylate part of the primary amines in the linear poly-α-lysine, thereby obtaining partially guanylated linear poly-α-lysine. The specific preparation method includes: adding 0.73 g of 1H-pyrazole-1-carboxamidine hydrochloride and 0.69 g of potassium carbonate to 80 g of an aqueous solution containing 2.5 wt% of linear poly-α-lysine; after replacing nitrogen three times, heating the mixed solution at 60°C for 12 h, then precipitating with ether, and vacuum drying to obtain partially guanylated linear α-lysine. The repeating units containing amino groups and the repeating units containing guanidine groups are randomly distributed in the polymer chain segments, and the mass ratio between the two is 1:1.
[0096] Cationic polymer B5
[0097] Branched lysine-arginine copolymer
[0098] The preparation method is different from the preparation method of branched polylysine only in that 91.32 g of lysine hydrochloride is replaced by an equal mass of lysine hydrochloride and arginine mixed monomers (the molar ratio of the two is 1:1), and the other steps are the same.
[0099] Cationic polymer B6
[0100] Linear poly α-lysine quaternary ammonium salt
[0101] The preparation method comprises: dissolving 5 g of N, N-dimethyldodecyl (2-acrylamideethyl) ammonium bromide in 200 mL of deionized water, adding 10 g of linear poly-α-lysine, reacting at 40°C for 24 h, and precipitating the obtained reaction mixture in ether and centrifuging to obtain a yellow solid, which is dissolved in water and then freeze-dried to obtain a linear poly-α-lysine quaternary ammonium salt.
[0102] Cationic polymer B7
[0103] Branched lysine quaternary ammonium salt
[0104] The preparation method is different from the preparation method of linear poly-α-lysine quaternary ammonium salt only in that 10 g of linear poly-α-lysine is replaced by an equal mass of branched poly-lysine, and the other steps are the same.
[0105] Cationic polymer B8
[0106] The preparation method of guanylated branched polylysine comprises: adding 1.46 g of 1H-pyrazole-1-carboxamidine hydrochloride and 1.38 g of potassium carbonate to 80 g of an aqueous solution containing 2.5 wt% of branched polylysine; after replacing nitrogen three times, heating the mixed solution at 60°C for 12 h, then settling with ether, and vacuum drying to obtain guanylated branched polylysine, which is a guanylated derivative of branched polyamino acids.
[0107] Cationic polymer B9
[0108] Polyhexamethylene biguanide hydrochloride: purchased from Maclean, product number P832584.
[0109] Cationic polymer B10
[0110] Aminoethyl methacrylate and 2-indoleethyl methacrylate copolymer (AEMA-co-IEMA)
[0111] The preparation method comprises: dissolving 331 mg of 2-aminoethylmethacrylate (AEMA), 229 mg of 2-(1H-indol-3-yl)ethyl methacrylate (IEMA), 7 mg of azobisisobutyronitrile (AIBN) and 81 mg of chain transfer agent 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid in 3 mL of dimethyl sulfoxide (DMSO), and heating the mixture under high vacuum (10 °C). -3 Torr) for three freeze-pump-thaw cycles, then heated to 70°C for 8 h. The obtained product was purified by three methanol-ether precipitations, centrifuged three times, and dried to obtain a copolymer of aminoethyl methacrylate and 2-indoleethyl methacrylate, which belongs to the acrylic acid ester copolymer containing quaternary ammonium groups.
[0112] Cationic polymer B11
[0113] Polycarbonate containing quaternary ammonium groups
[0114] The preparation method includes: using a glove box, 448 mg of functionalized cyclocarbonate monomer 2,2-bishydroxymethylformal propionic acid p-chloromethylbenzyl alcohol ester (MTC-OCH2BnCl), 22.2 mg of N-(3,5-trifluoromethylbenzene)-N′-cyclohexylthiourea (1-(3,5-bis(trifluoromethyl)-phenyl)-3-cyclohexyl-2-thiourea) and 2 mL of dry dichloromethane are mixed, and then 7.32 mg of 4-methylbenzyl alcohol is added to the mixture, and then 8.96 μL of bicyclic amidine is added thereto, and stirred at room temperature for about 30 minutes, and then an excess of benzoic acid (10 mg) is added to quench the catalyst. The obtained crude product is precipitated into cold methanol twice, and the supernatant is decanted to obtain polycarbonate. The polycarbonate was then quaternized by dissolving 0.35 g of polycarbonate in 10 mL of acetonitrile, adding an excess of a quaternizing agent (N-dimethylhexyl ammonium chloride), and stirring the reaction mixture at room temperature overnight. After quaternization, the crude product was then purified by dialysis using a 1:1 acetonitrile and isopropanol solvent system. After removing the solvent, the resulting polymer was freeze-dried to obtain a polycarbonate containing a quaternary ammonium group.
[0115] Cationic polymer B12
[0116] Chitosan: purchased from Maclean, product number C850346.
[0117] Cationic polymer B13
[0118] Polyacrylamide: purchased from Sigma-Aldrich, product number 738743.
[0119] The moisture content of the condensed particles provided by the present invention is 0.2%.
[0120] Example 1
[0121] The present embodiment provides a condensed particle, which includes a vinyl polymer A1 and a cationic polymer B6; based on 100 parts of the added amount of the vinyl polymer A1, the added amount of the cationic polymer B6 is 8.5 parts, and the parts are calculated based on the dry basis of the vinyl polymer and the dry basis of the cationic polymer.
[0122] This embodiment provides a method for preparing agglomerated particles, comprising the following steps:
[0123] Cationic polymer B6 is mixed with water to obtain a cationic polymer aqueous solution with a solid content of 4.3%; concentrated sulfuric acid is used to adjust the latex of vinyl polymer A1 to neutrality, and then at 75°C, according to the formula, the latex of vinyl polymer A1 is added to the cationic polymer aqueous solution in 4 times, and the amount added each time is 25% of the total amount of latex; then the obtained mixture is maintained at 75°C for 5 minutes, the temperature is increased to 95°C at a heating rate of 5°C / min and maintained for 10 minutes, and then the temperature is reduced to room temperature at a cooling rate of 2°C / min to obtain a coagulation slurry; the coagulation slurry is dehydrated by a centrifugal dehydrator, and then dried on a boiling bed at 60°C to obtain the coagulated particles.
[0124] Examples 2 to 24, Comparative Examples 1 to 4
[0125] Examples 2 to 24 and Comparative Examples 1 to 4 respectively provide a kind of condensed particles, which differ from Example 1 only in that the type of vinyl polymer, the type of coagulant and the content are different. The specific formulas are shown in Tables 2, 3, 4 and 5, wherein " / " indicates that the component is not included in the formula; in particular, for Example 23, in order to improve the solubility of the cationic polymer B12, B12 is configured into a cationic polymer aqueous solution of the same concentration using a 2% mass fraction of acetic acid aqueous solution; Comparative Example 3 uses concentrated sulfuric acid as the coagulant, which cannot completely demulsify. During solid-liquid separation, the liquid part still contains a large amount of latex, and the aqueous phase is milky white. When used, only the demulsified part is taken, while the other examples and comparative examples are completely demulsified during the coagulation process, and the aqueous layer is a clear and transparent yellow to light yellow solution during solid-liquid separation.
[0126] Table 2
[0127]
[0128] Table 3
[0129]
[0130] Table 4
[0131]
[0132] Table 5
[0133]
[0134] Application Examples
[0135] This application example provides a resin composition, which includes, by weight, 20 parts of an impact modifier and 80 parts of a SAN resin (resin grade KFA-130, Liaoning Jinfa); the impact modifier is the agglomerated particles provided in Examples 1 to 24 and Comparative Examples 1 to 4, respectively.
[0136] Control group 1: In the present invention, SAN resin (resin brand KFA-130, Liaoning Jinfa) without adding agglomerated particles is used as control group 1.
[0137] Performance Testing
[0138] (1) Oxidation induction time (OIT): The oxidation induction time of agglomerated particles was tested according to the national standard GBT 19466.6-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 6: Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)". Specifically, OIT was tested under isothermal conditions of 200°C in an air atmosphere.
[0139] (2) Resistance to heat aging and yellowing: The dried agglomerated particles were placed in multiple aluminum foil watch glasses and placed in a constant temperature oven at 180°C. After 24 hours of constant temperature, the samples were taken out and the b value of the agglomerated particles was tested using a Lab colorimeter. The larger the b value, the worse the resistance to heat aging and yellowing.
[0140] (3) Impact resistance: The resin composition including the agglomerated particles is mixed by a twin-screw extruder, and the resin composition is injection molded into a standard specimen with a notch according to the requirements of "GB / T 1843-2008 Determination of Izod impact strength of plastics" and its Izod notch impact strength is tested.
[0141] (4) Antibacterial and antifungal properties: The resin composition including the agglomerated particles was mixed by a twin-screw extruder, and pressed into sheets on a flat vulcanizer at an upper and lower plate temperature of 200° C. to prepare a sheet of (50±2) mm×(50±2) mm with a thickness not exceeding 10 mm, and the antibacterial and antifungal properties of the resin composition were tested;
[0142] The antibacterial performance is tested with reference to the national standard GB T 31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces for Antibacterial Performance of Materials". Specifically, the antibacterial test adopts the film method, and the operation steps are as follows: After the sample to be tested is disinfected, a bacterial suspension is inoculated on its surface and covered with a polyethylene film to form a uniform liquid film between the sample and the film. After culturing under certain conditions, it is eluted and diluted into an appropriate concentration gradient. A certain volume is applied to the culture medium for re-culturing and the number of viable bacteria is determined to calculate the antibacterial rate. The antibacterial rate calculation formula is: Antibacterial rate % = (the number of bacteria of a pure resin sample after 24 hours - the number of bacteria of the corresponding embodiment or comparative sample after 24 hours) / the number of bacteria of a pure resin sample after 24 hours * 100%. Detection bacteria: Escherichia coli ATCC 25922.
[0143] The anti-mildew performance is tested with reference to the national standard GB21551.2-2010 "Special requirements for antibacterial materials with antibacterial, sterilization and purification functions for household and similar electrical appliances"; among them, 0 represents the highest anti-mildew level, and 3 represents the lowest anti-mildew level.
[0144] The specific test results are shown in Table 6, where “-” means no test was performed.
[0145] Table 6
[0146]
[0147] In summary, the condensed particles provided by the present invention use a cationic polymer with a nitrogen-containing functional group as a coagulant, and the ratio of the cationic polymer to the vinyl polymer is within a specific range, and the obtained condensed particles have good heat-oxidative aging resistance, a long oxidation induction period and a low yellowing index; the condensed particles are used as an impact modifier, which can effectively improve the impact resistance, heat-oxidative resistance and aging yellowing resistance of the resin composite material, and at the same time, make the resin composite material have excellent antibacterial and mildew-proof properties; the oxidation induction period of the latex condensed particles in an air atmosphere and isothermal conditions of 200°C is ≥30 min, and after being continuously baked at 180°C in an oven for 24 hours, the condensed particles obtained by the present invention are whiter in color than those of the comparative example, and the b value is less than 10; the resin composition including the condensed particles has a cantilever beam notched impact strength of more than 24 kJ / m 2 ; The antibacterial rate is over 80%, and the mildew resistance level is 0~1.
[0148] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A condensed particle, characterized in that: The condensed particles include a vinyl polymer and a condensing agent; The coagulant includes a cationic polymer; The cationic polymer has a nitrogen-containing functional group in its molecular structure; The amount of the cationic polymer added is 0.2 to 27 parts based on 100 parts of the vinyl polymer added; The nitrogen-containing functional group includes at least one of an amide group, an amine group, an ammonium group, a guanidine group or a nitrogen-containing aromatic group; The molecular structure of the vinyl polymer includes any one or a combination of at least two of a structural unit derived from a conjugated diene, a structural unit derived from styrene and its derivatives, a structural unit derived from acrylonitrile and its derivatives, or a structural unit derived from an alkyl (meth)acrylate; The cationic polymer includes at least one of chitosan, polyamino acid and its derivatives, polyhexamethylene biguanide and its salts, acrylic acid ester polymers containing quaternary ammonium groups or polycarbonate polymers containing quaternary ammonium groups.
2. The agglomerated particles according to claim 1, characterized in that Based on 100 parts of the vinyl polymer, the amount of the coagulant added is 2 to 18 parts.
3. The agglomerated particles according to claim 1, characterized in that The polyamino acids and their derivatives include at least one of linear homopolymeric polyamino acids, linear copolymeric polyamino acids, branched homopolymeric polyamino acids, branched copolymeric polyamino acids, quaternized derivatives of polyamino acids, guanidinated derivatives of polyamino acids, or quaternized and guanidinated derivatives of polyamino acids.
4. The agglomerated particles according to claim 3, characterized in that In the quaternized derivative of polyamino acid, the guanidated derivative of polyamino acid or the quaternized and guanidated derivative of polyamino acid, the mass percentage of repeating units containing quaternary ammonium groups and / or repeating units containing guanidine groups is 50-100%.
5. The agglomerated particles according to claim 3, characterized in that The monomers in the linear homopolymeric amino acid and the branched homopolymeric amino acid independently include any one of lysine, arginine, alanine, isoleucine, phenylalanine, tryptophan, histidine and glutamine.
6. The agglomerated particles according to claim 3, characterized in that The monomers in the linear copolymerized amino acid and the branched copolymerized amino acid independently include at least two of lysine, arginine, alanine, isoleucine, phenylalanine, tryptophan, histidine and glutamine.
7. The agglomerated particles according to claim 3, characterized in that The monomers in the linear copolymerized amino acid and the branched copolymerized amino acid each independently include at least arginine.
8. The agglomerated particles according to claim 1, characterized in that The molecular structure of the vinyl polymer includes structural units derived from conjugated dienes and structural units derived from styrene and its derivatives, and also includes at least one of structural units derived from acrylonitrile and its derivatives and structural units derived from alkyl (meth)acrylates.
9. The agglomerated particles according to claim 8, characterized in that In the vinyl polymer, the mass percentage of the structural units derived from conjugated dienes is 50-80%, the mass percentage of the structural units derived from styrene and its derivatives is 5-25%, and the balance is structural units derived from acrylonitrile and its derivatives, and / or structural units derived from alkyl (meth)acrylates.
10. The agglomerated particles according to claim 1, characterized in that The oxidation induction period of the agglomerated particles in an air atmosphere at an isothermal temperature of 200° C. is ≥30 min; The ab value of the agglomerated particles measured by a Lab colorimeter is ≤10.
11. A method for preparing agglomerated particles according to any one of claims 1 to 10, characterized in that: The preparation method comprises the following steps: The agglomerated particles are obtained by mixing a latex of a vinyl polymer with a coagulant, subjecting the mixture to agglomeration and drying.
12. The preparation method according to claim 11, characterized in that: The coagulation is carried out under neutral conditions.
13. The preparation method according to claim 11, characterized in that: The condensation includes condensation through the steps of first heat preservation, temperature increase, second heat preservation and temperature reduction; The first insulation temperature is 70-80°C and the time is 1-10 min; The heating rate of the heating is 3-7°C / min; The second insulation temperature is 90-100°C and the time is 5-15 min; The cooling rate is 0.5-4°C / min, down to room temperature.
14. A resin composition, characterized in that In parts by weight, the resin composition comprises 70 to 90 parts of resin and 10 to 30 parts of impact modifier; The impact modifier comprises the agglomerated particles according to any one of claims 1 to 10.
15. The resin composition according to claim 14, characterized in that The resin comprises at least one of styrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene-acrylonitrile terpolymer, polystyrene, polyvinyl chloride, polycarbonate, polypropylene, polyphenylene ether, polyester or polyamide; The antibacterial rate of the resin composition is ≥80%, and the mildew resistance level reaches 0-1; The resin composition has an Izod notched impact strength of ≥24 kJ / m 2 .
Citation Information
Patent Citations
Polymer latex agglomerated particles and preparation method thereof
CN114085338A